The interrelationships between parental migration, home environment, and early child development in rural China: A cross-sectional study - Jingdong Zhong; Lena Kuhn; Tianyi Wang; Chengfang Liu; Renfu Luo (International Journal of Environmental Research and Public Health, 2020)
A growing body of literature is providing evidence of a negative association between parental migration and child development. Meanwhile, the chain of relationships between parental migration, home environment, and early child development has not yet been well documented in China. This paper investigates the interrelationships between parental migration, home environment, and early child development in an undeveloped area of western rural China. In total, 444 households were included in the study. Bayley Scales of Infant Development version III (BSID-III), Home Observation Measurement of the Environment (HOME), and a socioeconomic questionnaire, were used to measure children's development outcomes, home environment, and socioeconomic characteristics in sample households. A mediation effect model was used to estimate the interrelationships between parental migration, home environment, and child development. The results demonstrate that home environment works as a significant mediator, through which parental migration is associated with a 0.07 standard deviation (SD), 0.13 SD, 0.12 SD, and 0.10 SD decline in the child's cognitive, language, motor, and social-emotional scores, respectively. For future studies, the key findings suggest that interventions aimed at improving the home environments of left-behind children might be necessary in rural China.
Keywords: 330; parental migration; home environment; early child development